Pharmacologic properties and inhibitory activity of 6-azasteroids against Mycobacterium leprae in vivo and in vitro - Thabatta L. S. A. Rosa; Maria Angela M. Marques; Tianao Yuan; Daniele F. F. Bertoluci; Joshua Werman; Fabricio da M. R. Costa; Linda A. Fischbacher; Mariana de Andrea Hacker; Ramanuj Lahiri; Márcia Bêrredo-Pinho; Patrícia S. Rosa; John T. Belisle; et al. (Microbiology Spectrum)
ABSTRACT Although the current multidrug therapy (MDT) for leprosy is very successful, the long treatment duration and the emergence of antibiotic-resistant strains demand for new alternative drugs. One potential target for drug development against pathogenic mycobacteria is their need to degrade host cholesterol during infection. Mycobacterium leprae, due to its degenerate genome, has preserved only the first step of cholesterol catabolism, in which cholesterol is oxidized to cholestenone by the enzyme 3β-hydroxysteroid dehydrogenase (3β-HSD). M. leprae avidly produces cholestenone in vivo, and this metabolic activity seems to play an important role in bacterial pathogenesis. In this study, six 6-azasteroid analogs were developed with the potential to inhibit 3β-HSD, and their metabolic stability and in vitro and in vivo inhibitory activity against M. leprae were investigated. Pharmacologic properties indicated lower metabolic liabilities for azasteroid 5 in comparison to its progenitors, azasteroids 1 and 2, resulting in improved accumulation and extended t1/2 values in mice. Azasteroid 5 also partially inhibits M. leprae 3β-HSD in vitro. When tested in the Shepard’s mouse footpad model of leprosy, azasteroid 5 showed effective bacterial killing that was accelerated when combined with a subinhibitory dose of rifampicin and exhibited an absence of detectable hepatotoxic effects. We concluded that 6-azasteroids derivatives are promising new antimicrobial candidates for leprosy treatment.IMPORTANCELeprosy remains a significant global health challenge, particularly in underserved regions. While multidrug therapy (MDT) has been effective, its prolonged duration and the emergence of antibiotic-resistant strains emphasize the urgent need for novel therapeutic strategies. Recent advances in understanding Mycobacterium leprae’s unique biology have identified cholesterol metabolism as a critical pathway for bacterial survival and pathogenesis, offering a promising new target for drug development. Building on insights from tuberculosis research, azasteroids—compounds known for their potential to disrupt mycobacterial cholesterol metabolism—are now being explored as candidates for leprosy treatment. These molecules inhibit M. leprae’s cholesterol oxidation, impairing bacterial persistence within the host. This innovative approach could lead to more effective, faster-acting therapies, overcoming current treatment limitations and resistance. Such efforts represent a vital step forward in reducing the burden of leprosy and empowering affected communities worldwide.